18β-Glycyrrhetinic acid inhibits the apoptosis of cells infected with rotavirus SA11 via the Fas/FasL pathway - Xiaoyan Wang; Fang Xie; Xiaofeng Zhou; Ting Chen; Ye Xue; Wei Wang (Taylor & Francis Group, 2021)
Context 18β-Glycyrrhetinic acid (18β-GA), a pentacyclic triterpenoid saponin metabolite of glycyrrhizin, exhibits several biological activities. Objective We investigated the effects of 18β-GA on MA104 cells infected with rotavirus (RV) and its potential mechanism of action. Materials and methods Cell Counting Kit-8 was used to assess tissue culture infective dose 50 (TCID50) and 50% cellular cytotoxicity (CC50) concentration. MA104 cells infected with RV SA11 were treated with 18β-GA (1, 2, 4, and 8 μg/mL, respectively). Cytopathic effects were observed. The virus inhibition rate, concentration for 50% of maximal effect (EC50), and selection index (SI) were calculated. Cell cycle, cell apoptosis, and mRNA and protein expression related to the Fas/FasL pathway were detected. Results TCID50 of RV SA11 was 10−4.47/100 µL; the CC50 of 18β-GA on MA104 cells was 86.92 µg/mL. 18β-GA showed significant antiviral activity; EC50 was 3.14 μg/mL, and SI was 27.68. The ratio of MA104 cells infected with RV SA11 in the G0/G1 phase and the G2/M phase decreased and increased, respectively, after 18β-GA treatment. 18β-GA significantly induced apoptosis in the infected cells. Furthermore, after 18β-GA treatment, the mRNA and protein expression levels of Fas, FasL, caspase 3, and Bcl-2 decreased, whereas the expression levels of Bax increased. Discussion and conclusions The study demonstrates that 18β-GA may be a promising candidate for the treatment of RV SA11 infection and provides theoretical support for the clinical development of glycyrrhizic acid compounds for the treatment of RV infection.